2010
DOI: 10.3357/asem.2427.2010
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Herniated Nucleus Pulposus Among U.S. Astronauts

Abstract: Astronauts are at higher risk of incurring HNP, especially immediately following spaceflight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
131
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 0 publications
1
131
1
5
Order By: Relevance
“…Although we cannot rule out an impact of spaceflight on medium to long-term IVD degeneration post-flight in the relatively short duration of a spaceflight the IVD is not likely to degenerate. Thus, the spike of IVD herniation incidence observed by Johnston et al [1] immediately after spaceflight emphasises the mechanics of internal IVD forces and influence of external forces on IVD herniation.…”
Section: What Can Astronaut Ivd Herniations Tell Us About Herniationsmentioning
confidence: 91%
See 4 more Smart Citations
“…Although we cannot rule out an impact of spaceflight on medium to long-term IVD degeneration post-flight in the relatively short duration of a spaceflight the IVD is not likely to degenerate. Thus, the spike of IVD herniation incidence observed by Johnston et al [1] immediately after spaceflight emphasises the mechanics of internal IVD forces and influence of external forces on IVD herniation.…”
Section: What Can Astronaut Ivd Herniations Tell Us About Herniationsmentioning
confidence: 91%
“…Apollo and Shuttle astronauts (top panels) walked immediately after landing, whereas astronauts and cosmonauts coming back with the Soyuz vessel (bottom panels) were carried out of the capsule. The data presented by Johnston et al [1] suggested that those astronauts who performed upright activities immediately after spaceflight were at a higher risk of IVD herniation. Photo credits: NASA (top left and right, bottom right), ESA (bottom left) their previous sporting pursuits, are at risk for IVD problems.…”
Section: Cumulative Injury To the Ivd Prior To Spaceflightmentioning
confidence: 99%
See 3 more Smart Citations